Profile of the elderly who attend companionship groups in Sinop-MT - Masochini, R. G.; Jezus, S. V.; Cunha, A. N.; Fanin, P. C. (Scientific Electronic Archives, 2018)
The Brazilian population aging in recent decades has led to the creation and implementation of public policies aimed at guaranteeing the social rights of the elderly. The need to implement strategies that provide autonomy, social integration and quality of life for this age group has become increasingly urgent. This study aimed to describe the socio-economic, familial and health profiles of the elderly who participate in a companionship group in the municipality of Sinop-MT. Data collection were performed through a multiple choice questionnaire Brazil Old Age Schedule (BOAS). This is a cross-sectional study with a quantitative approach. The sample consisted of 49 elderly participants of the elderly companionship group. Data collection was performed from April 20 to May 20, 2017. The results indicated that 27 (55.10%) were women, 28 (57.14%) widowers, 37 (75.50%) had finished primary school, 32 (65.30%) were retired and 22 (89%) had income between two and three minimum wages per month. 29 (59.1%) reported never feeling lonely and 46 (93.8%) did not feel depressed. 77.55% (n = 38) reported living alone and being solely responsible for household income; 75.51% (n = 37) said they were satisfied with the family relationship. (61.22%) evaluated their health as good, 81.63% (n = 40), had a confirmed diagnosis of disease, 69.38% (n = 34) reported using at least one medication and 79.59% (n = 39) reported excellent willingness to perform activities. With the purpose of obtaining subsidies that make possible the local planning of the actions directed to this population, through this study it is concluded that the participation of the elderly in companionship groups promotes a more active life and the inclusion of these individuals in social activities, so that the same ones exchange experiences, broaden their means of conviviality, improve their self-esteem and enjoy a quality old age.